3D continuous copper networks coated with graphene in Al-matrix composites for efficient thermal management. (15th February 2021) - Han, Xiaopeng; Huang, Ying; Peng, Xuanyi; Gao, Xiaogang; Li, Tiehu; Liu, Panbo
Abstract: Thermal management is a crucial issue for the reliability and life of the electronic devices. In this study, we successfully fabricated aluminum (Al) matrix composites with Cu networks (CNs) using a straightforward way. Graphite flakes (GFs) and CNs coated with graphene (CNs@Gr) were used to improve the performance of Al-matrix composites by hot-pressing method. There-dimensional (3D) CNs@Gr in the composites displayed an effective thermal transfer pathway in the matrix. The thermal conductivity (TC) of Al/GFs/CNs@Gr-5 composites (482.14 W/m·K) at a low Gr content, which has increased about 103.4% compared to pure Al. The synthesized CNs@Gr networks with continuous dendritic structure can serve as high-efficiency thermal transfer pathways to enhance heat dissipation through Gr layers, which reduced interfacial resistance for phonon scatterings. Furthermore, all fabricated composites displayed a lower coefficient of thermal expansion (less than 2.5 × 10 −5 ) (CTE) than pure Al matrix (below 340℃). As a result, the construction of 3D networks in Al-matrix composites with high comprehensive performance makes them promising thermal management materials.